If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = -2 + -1y Solving 9 = -2 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. 9 + y = -2 + -1y + y Combine like terms: -1y + y = 0 9 + y = -2 + 0 9 + y = -2 Add '-9' to each side of the equation. 9 + -9 + y = -2 + -9 Combine like terms: 9 + -9 = 0 0 + y = -2 + -9 y = -2 + -9 Combine like terms: -2 + -9 = -11 y = -11 Simplifying y = -11
| 34x-13=55 | | 16a+2b=4 | | -15=5m^2+28m | | Y=8x^2+2x-3 | | -1x+3=-8 | | n+n+1+n+2=54 | | -6-2x=10-8 | | .25x+8=.62x+2 | | 15/(8n-32) | | 11x-33=8x+0 | | 2x^2-7x-70=3x | | 5p+2=4p-9 | | (-18)+q=5 | | 2t^2+5=2t^2+1 | | n+n+1+n+1=54 | | 15/8n-32 | | -5.9=k/3 | | 25m^2+2=3 | | 7-3x=5x+14 | | 10x-50=25 | | 3x-6x^2/x^3 | | x*0.65=28748 | | 100-38= | | 2x^2+31-9=0 | | a+2a+3a-b=7a-6 | | 5x-1=15x-72 | | 9(x+12)=18 | | 9=8+z | | 6k+2.3=-9.7 | | 2(2x-4)=3(x+3) | | 5x^2-22=8x | | m+9=4m+12 |